Development Innovations through Entrepreneurial Microfinance and the Attempt to Achieve the United Nations Millennium Development Goals in Bangladesh - Saleh Ahmed (Advances in Social Work, 2012)
As one of the countries in the Global South, Bangladesh has experienced numerous development challenges since its liberation in 1971. Bangladesh has showcased how to fight against poverty and to initiate meaningful change and development in human lives. Nobel Prize (2006) winner Grameen Bank is one of the popular development innovations in the country. Since the beginning of this Bank in the early 1970s, microfinance and entrepreneurship development with small amounts of money have proliferated to nearly every corner of the globe with the paramount goal of alleviating global poverty and ensuring human development. Like all other new social science techniques, the societal revolution brought about by microfinance expansion has left substantial room for refinement and further support by empirical evidence. This article critically evaluates a non-governmental initiative to empower extremely poor women through entrepreneurial microfinance, and examines the socioeconomic impacts in achieving the United Nations Millennium Development Goals (UNMDGs). This article covers both primary and secondary information. The aim is to demonstrate how countries of the Global South can use carefully designed microfinance projects to address major development challenges and meaningfully contribute to creating a more equal, humane society.